1995
DOI: 10.1111/j.1600-0560.1995.tb01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic clear cell acanthoma

Abstract: An histologically typical clear cell acanthoma was identified forming a cystic structure. The finding of clear cell acanthoma within a cyst is histologically unique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…It appears mainly on the lower leg as a slightly elevated, dome‐shaped, erythematous nodule with thin wafer‐like scales providing a peripheral collarette. Variant forms of CCA have been reported, including giant (3, 4), multiple (5, 6), cystic (7), and pigmented (8) cases, and those associated with epidermal nevus (9, 10) and melanocytic nevus (11). Polypoid CCA has also been reported by some authors (11–15).…”
Section: Discussionmentioning
confidence: 99%
“…It appears mainly on the lower leg as a slightly elevated, dome‐shaped, erythematous nodule with thin wafer‐like scales providing a peripheral collarette. Variant forms of CCA have been reported, including giant (3, 4), multiple (5, 6), cystic (7), and pigmented (8) cases, and those associated with epidermal nevus (9, 10) and melanocytic nevus (11). Polypoid CCA has also been reported by some authors (11–15).…”
Section: Discussionmentioning
confidence: 99%
“…The common locations of CCA include the leg, thigh, back, abdomen and chest 5 . Uncommon locations include the nipple, 6,24 vermilion mucosa of lower lips, 53 hallux/toe, 54 palm, 49 genitalia, 21 scrotum, 37 suprapubic, 47 umbilicus 50 and scalp 35…”
Section: Clinical Presentation and Variantsmentioning
confidence: 99%
“…There is only one report of this variant in the English literature. Hamaguchi et al 47 reported a case of cystic CCA in the suprapubic area of a middle-aged man. On histopathological examination, the lesion was diagnosed as a typical CCA with cystic hair shafts, which was surrounded by a condensed connective-tissue sheath.…”
Section: Cystic Clear Cell Acanthomamentioning
confidence: 99%
“…Multiple CCA are uncommon and predominantly located on legs, but they may appear on head, torso, and upper limbs 3 . Other unusual clinical types include giant, polypoid, pigmented, and cystic CCA 1,2,4,5 . CCA has developed on pre‐existing lesions (e.g.…”
Section: Unusual Locations and Variants Of Clear Cell Acanthoma (Cca)mentioning
confidence: 99%